2013
DOI: 10.1177/0022034513513026
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Bone Marrow Mesenchymal Stem Cell Transplantation for Periodontal Regeneration

Abstract: In this study, we investigated the possibility of using local administration of allogeneic bone marrow mesenchymal stem cells (BMMSCs) to induce tissue regeneration in periodontal defects in a rat model of periodontitis. BMMSCs isolated from rats were mixed with 0.9% NaCl solution and injected into periodontal defects. Control groups were 0.9% NaCl solution or left untreated. The clinical assessments, x-rays, and histological examinations were used to evaluate the effect. At 12 wks post-transplantation, quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 30 publications
(32 reference statements)
1
111
0
2
Order By: Relevance
“…2). The regenerative potential of autologous and allogeneic PDLSCs, as well as of DPSCs, SHEDs and bone marrow stem cells for the treatment of periodontitis has been also demonstrated in other animal models, such as the miniature swine and dog models (Ding et al, 2010;Du et al, 2014;Fu et al, 2014;Khorsand et al, 2013). In TA Mitsiadis et al Stem cells for dental clinical use Fig.…”
Section: Regeneration Of Periodontal Tissuesmentioning
confidence: 96%
See 3 more Smart Citations
“…2). The regenerative potential of autologous and allogeneic PDLSCs, as well as of DPSCs, SHEDs and bone marrow stem cells for the treatment of periodontitis has been also demonstrated in other animal models, such as the miniature swine and dog models (Ding et al, 2010;Du et al, 2014;Fu et al, 2014;Khorsand et al, 2013). In TA Mitsiadis et al Stem cells for dental clinical use Fig.…”
Section: Regeneration Of Periodontal Tissuesmentioning
confidence: 96%
“…Currently, missing teeth are replaced with dental implants (Esposito et al, 2013). Their retention requires close contact of implants with the alveolar bone, a process called osseointegration (Branemark et al, 1977).…”
Section: Current Therapeutic Interventions In Dentistrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, Zhang et al reported that BMSCs exhibited stronger osteogenic differentiation than PDLSCs stimulated with the inflammatory cytokine TNF-α in vitro, indicating that BMSCs might have better immunomodulatory properties in the local microenvironment compared with PDLSCs [57]. Allogeneic BMSC transplantation into a mouse periodontal defect model has been reported to regenerate bone, cementum, and PDL while integrating into all three newly formed tissues [58], and locally suppress the expression of inflammatory cytokines, including TNF-α and IL-1 [59]. These findings suggest that BMSC transplantation could also be feasible for periodontal regeneration, especially in alveolar bone regeneration under inflammatory conditions like those that occur after periodontal surgery for chronic periodontitis.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%